(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Kanyashree Prakalpa 2013, a CCT scheme for improving the status and well being of the girl child in the state has been formulated and implemented by the Department of Women Development and Social Welfare, Government of West Bengal. The department of DWD SW observed that girl child marriage is a social menace and the socio-economic problem is the moot point behind it. Therefore if poor parents are supported with a substantial economic package then they can take recourse to getting their daughters married off at an early age. Kanyashree Prakalpa has started functioning in two ways – it helps poor parents to marry off their daughters though not forcibly, and it motivates such parents to encourage their daughters to study for their bright future. Under this backdrop, present study was conducted in Chakdah Haringhata blocks of Nadia district of West Bengal. The present paper was an effort to assess the attitude of parents and teachers towards Kanyashree Prakalpa. To explore the Attitude of Father (N= 45), Mother (N= 45) and teacher (N= 40) towards Kanyashree Prakalpa, data were collected using a structured interview which was based on ten questions highlighting ten areas to be covered. Findings, as determined from the content analysis of interviewed data, indicate greater percentage of positive attitude of parents and teachers towards Kanyashree Prakalpa scheme. 97 per cent father and 71 per cent mother appreciated this scheme but, most interestingly below 50 teachers did not appreciate this scheme.